Book Review: Flinthandwerk by Wulf Hein and Marquardt Lund - Philipp Schraut (EXARC, 2018)
The book “Flinthandwerk” is a co-production of two known German experts in experimental archaeology. Both authors have been studying prehistoric techniques for years; Lund has spent his whole lifetime practicing flint-knapping skills during his free time, whilst Hein is the founder of a company that specializes in the reproduction of Stone Age artifacts for museums. Lund is the initiator of the European flint-knapping conference that takes place every year.